Analysis of subcarrier intensity modulation‐based optical wireless DF relaying over turbulence channels with path loss and pointing error impairments. Issue 17 (1st November 2014) - Aggarwal, Mona; Garg, Parul; Puri, Parul
Abstract : The authors consider a subcarrier intensity‐modulated relayed optical wireless communication system under the combined influence of path loss, atmospheric turbulence and pointing error impairments. The turbulence‐induced fading is modelled by independent but not necessarily identically distributed (i.n.i.d.) Gamma–Gamma fading statistics where the relaying protocol followed by the system is decode and forward (DF). First, the statistics of instantaneous signal‐to‐noise ratio at the destination is derived, followed by the novel and exact closed‐form expression for outage probability of the system. Then using the moment generating function‐based approach, the authors evaluate error performance of the system in terms of average symbol error rate (SER) for M‐ary phase shift keying modulation schemes. Further, as a special case for M = 2, that is, binary phase shift keying modulation scheme, the exact closed‐form expression of average SER is derived in terms of mathematically tractable Meijer's G‐function and extended generalised bivariate Meijer's G‐function. Finally, at the end of the paper, various numerical examples are included to demonstrate the effect of different system parameters on the performance of the system and are verified by Monte‐Carlo simulations.